Floristic-phytosociological approach, potential natural vegetation, and survival of prejudice - Mucina, Ladislav (Lazaroa, 2011)
Carrion & Fernandez (2009; further C&F) in a recent commentary on a paper published in Journal of Biogeography criticised an obvious mismatch between the predictions about the patterns of potential natural vegetation (PNV) made by phytosociologists, and those underpinned by pollen data. C&F used this stage to take a broad sway on phytosociology in general (stopping only very short of denying it status of science), blaming power of tradition and influence of personal cult for ignoring scientific evidence. In my response I show that C&F have misinterpreted the concept of PNV, rendering their comparisons irrelevant. C&F obviously overslept the progress descriptive vegetation science made in recent decades, relegating their heavy criticism of phytosociology into the realm of prejudice.